Sequestration rate of heavy metal contaminants using riccia fluitans as potential phytoremediation agent in polluted aquatic ecosystem - Othman, Rashidi; Hanifah, Nurul Azlen; Ramya, Razanah; Mohd Hatta, Farah Ayuni; Wan Sulaiman, Wan Syibrah Hanisah; Mohd. Yaman, Maheran; Hj. Baharuddin, Zainul Mukrim (Pak Publishing Group, 2014)
The application of green technology is the combination of the environmental science and technology in which helps the improvement and application of products, apparatus as well as the system to safeguard the natural resources and the environment. Aquatic plants have been increasingly being utilized as remarkably efficient and responsive apparatus for diagnosing and predicting environmental stresses. Thus, this research aimed to assess Riccia fluitans capability and potential as a phytoremediation agent to remediate heavy metal contamination in an unhealthy aquatic ecosystem. Subsequently, Riccia fluitans was exposed to three types of heavy metals (Mn, Zn and Pb) at three different concentrations (1.0, 2.0 and 5.0 mg l −1 ) at four different periods of time (week 1 to week 4). All heavy metals were analyzed through HACH DR5000 spectrophotometer. As a result, among five heavy metals tested, Riccia fluitans revealed as a good agent to sequester Mn, Zn and Pb respectively. The analysis affirmed the accumulation of different metals within the plant and an equally lessen of metals in the water. An eloquent equivalence between type of heavy metals and concentration, period of time and Riccia fluitans were attained. As a conclusion, Riccia Fluitans is proven to be a potential biosequester agent for polluted aquatic environment.